2008
DOI: 10.1159/000137689
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Quality of Life and Cognitive Decline in Dementia

Abstract: Aims: We aimed to examine the association of cognitive decline with quality of life (QoL) in dementia compared to controls and to determine variables associated with QoL. Methods: Every subject was placed within a specific group depending on their designation by the Mini Mental State Examination and evaluated by the Alzheimer’s Disease Related Quality of Life (ADRQL) and clinical assessments. Results: QoL for the mild dementia group was lower (p = 0.08) than that of controls. The very severe dementia group had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 79 publications
3
43
0
7
Order By: Relevance
“…In general, the relationship between cognitive impairment or dementia and quality of life is not uniform among different studies. Depending of the instruments, procedure, and setting, some authors did find an association between both dimensions [40][41][42] and other authors did not [43][44][45][46][47]. A similar situation occurs in PD, with studies showing a relationship between cognitive status and HRQoL [22,27,48,49], even in non-demented patients [50], and other studies which found only a weak association [51,52].…”
Section: Cognitive Deteriorationmentioning
confidence: 87%
“…In general, the relationship between cognitive impairment or dementia and quality of life is not uniform among different studies. Depending of the instruments, procedure, and setting, some authors did find an association between both dimensions [40][41][42] and other authors did not [43][44][45][46][47]. A similar situation occurs in PD, with studies showing a relationship between cognitive status and HRQoL [22,27,48,49], even in non-demented patients [50], and other studies which found only a weak association [51,52].…”
Section: Cognitive Deteriorationmentioning
confidence: 87%
“…It is generally assumed that cognitive impairment can affect quality of life, (Muangpaisan, Assantachai, Intalapaporn, & Pisansalakij, 2008;Missotten et al, 2008a;Missotten et al, 2008b;Barrios et al, 2013), but we could not identify previous studies that specifically compared health status between people with and without cognitive impairment in the general population (i.e. not specifically in patients with Table 2 Health status scores for total population and participants with and without cognitive impairment (mean ± SD).…”
Section: Discussionmentioning
confidence: 99%
“…Different dimensions of QoL may be relevant to different stages of dementia and the association between QoL and other variables such as depression, ADL, cognitive performance and behavioral symptoms may vary across the disease spectrum although there is indication that depression has an impact on QoL regardless of cognitive status [8,9] . Methodological limitations in the form of heterogeneity of scales used to measure QoL as well as variation in the type of rating (self, proxy, physician) have been denoted as important factors leading to such results [10] .…”
Section: Introductionmentioning
confidence: 99%